TGS1 impacts snRNA 3′-end processing, ameliorates survival motor neuron-dependent neurological phenotypes in vivo and prevents neurodegeneration. Issue 21 (10th August 2022) - Chen, Lu; Roake, Caitlin M; Maccallini, Paolo; Bavasso, Francesca; Dehghannasiri, Roozbeh; Santonicola, Pamela; Mendoza-Ferreira, Natalia; Scatolini, Livia; Rizzuti, Ludovico; Esposito, Alessandro; Gallotta, Ivan; Francia, Sofia; et al.
Abstract: Trimethylguanosine synthase 1 (TGS1) is a highly conserved enzyme that converts the 5′-monomethylguanosine cap of small nuclear RNAs (snRNAs) to a trimethylguanosine cap. Here, we show that loss of TGS1 in Caenorhabditis elegans, Drosophila melanogaster and Danio rerio results in neurological phenotypes similar to those caused by survival motor neuron (SMN) deficiency. Importantly, expression of human TGS1 ameliorates the SMN -dependent neurological phenotypes in both flies and worms, revealing that TGS1 can partly counteract the effects of SMN deficiency. TGS1 loss in HeLa cells leads to the accumulation of immature U2 and U4atac snRNAs with long 3′ tails that are often uridylated. snRNAs with defective 3′ terminations also accumulate in Drosophila Tgs1 mutants. Consistent with defective snRNA maturation, TGS1 and SMN mutant cells also exhibit partially overlapping transcriptome alterations that include aberrantly spliced and readthrough transcripts. Together, these results identify a neuroprotective function for TGS1 and reinforce the view that defective snRNA maturation affects neuronal viability and function.